Structural optimization and biological evaluation of 1,2,3-triazolic prototype with potent trypanocidal activity - Oliveira, Filipe Canto (2024)
After more than a century since its discovery, Chagas disease persists as a significant public health concern, predominantly impacting the most economically and socially vulnerable populations. Despite some advancements, the treatment of Chagas disease still relies on only two partially effective medications, benznidazole and nifurtimox, both of which come with severe side effects. In light of this reality, in a previous work, our research group synthesized 27 novel analogs of benznidazole, aiming for improved treatment alternatives. Among these analogs, G15 demonstrated activity against T. cruzi four times greater than benznidazole (IC50 7.0 ?M) and exhibited remarkably high selectivity (SI 114). However, its pharmacokinetic parameters, particularly solubility, were inadequate for in vivo studies. For this reason, this work was developed with the aim of overcoming these challenges and deepening our understanding of the activity and mechanism of action of G15. Thus, guided by computational predictions, 19 analogs of G15 were designed and synthesized and a liposome-encapsulated G15 solution was prepared. In addition to T. cruzi, these compounds were tested for activity against the parasites T. bruc., L. inf., and T. rhod., as well as the human pathogens Staphylococcus aureus, Candida albicans, and Pseudomonas aeruginosa. Notably, analog 29 emerged as the most promising compound, displaying significant activity against T. cruzi (IC50 5.58 ± 0.98 ?M), without causing any cytotoxicity in mammalian cells. Moreover, it exhibits a predicted Log Po/w value that is two times lower than G15 (1.41 vs. 0.70), potentially resolving the solubility challenges encountered before and enabling the continuation of the in vivo studies. An investigation into the interaction between G15 and T. cruzi nitroreductases (TcNTR) was also conducted to explore its mechanism of action; however, the results were inconclusive and new experiments are needed. Moreover, another 6 new compounds were provided to the Brazilian Institute of Energy and Nuclear Research (IPEN) for a collaborative research, aiming to explore their potential use in Chagas disease diagnosis through SPECT/PET/CT molecular imaging and their study is currently in progress.